Symptomatic Benign Prostatic Hyperplasia: A Risk Factor for Periprosthetic Joint Infection in Male Patients. (1st April 2020) - Yazdi, Hamidreza; Restrepo, Camilo; Foltz, Carol; Hammad, Mohammed; Chung, Paul H.; Gomella, Leonard G.; Parvizi, Javad
Abstract : Background: Male patients undergoing total joint arthroplasty have a higher risk of periprosthetic joint infection (PJI) compared with female patients. The exact reason for this finding is not well known. This study aimed to determine if patients with symptomatic benign prostatic hyperplasia (BPH) are at increased risk of PJI. Methods: A total of 12, 902 male patients who underwent primary or revision total joint arthroplasty from January 2006 to April 2017 were retrospectively identified. The mean patient age was 62.47 years and the mean patient body mass index was 30.1 kg/m 2 . The majority of patients were Caucasian or African American. Most surgical procedures involved the hip joints (57.8%) and were primary arthroplasties (86%). Of these patients, 386 (3%) had symptomatic BPH. Among this group, 250 patients with symptomatic BPH were identified and were matched in an approximate 1:3 ratio with 708 control patients. Using the International Consensus Meeting criteria, patients who developed PJI were identified. Results: The PJI rate was 7.9% in the symptomatic BPH group and 2.8% in the control group. Multivariate regression analysis in unmatched groups showed that symptomatic BPH was a strong independent risk factor for PJI. After matching for variables related to outcomes, symptomatic BPH remained a significant risk factor for PJI (p = 0.01). Conclusions: Patients with symptomatic BPH had a higher risk of PJI compared with the control patients. This may partly explain the higher rate of PJI that is seen in male patients. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.